CELLULOSE SYNTHESIS BY Acetobacter xylinum IN WATER AS AN ALTERNATIVE RESOURCE TO MAKE NATA - Jazirotul Fitriyati; Aisyah Hafira Rizal; Farahaura Febriana Hermawa (Bionatural : Jurnal Ilmiah Pendidikan Biologi, 2019)
Nata de coco is actually cellulose layers which is formed by bacteria Acetobacter xylinum. This bacteria is forming cellulose layer by metabolize simple carbohydrate such as  glucose into another form of carbohydrate which is more complex as cellulose.the avaibility of coconuts water as main resource of cultivation medium can be seasonal and unstable. Alternative resource that available in high amount in any season is needed to ensure that the production of nata would not stop due to limited resource. One of resource that available in abundant is water.There were three sets of experiment by using three recipes in this research. The first recipe and second recipe were actually the same recipe except the main resources, coconut water and water; respectively. the third recipe were using water with  twice amount of urea, glacial acetic acid, sugar, and bacteria starter from recipe number one.As the result, The forming of cellulose layer was run faster in coconut water compare to water. However, Water still can be used as an alternative resource to produce cellulose layer by following recipe number 2 is commonly used to make nata de coco. The forming of cellulose layer in water was begun at day 14th of incubation. Adding twice amount of acetic acid from the original recipe in water can inhibit the synthesis of cellulose by decreasing the pH below 3.5 that can stop  A. xylinum to grow. Keywords: cellulose synthesis, acetobacter xylinum , water, alternative resource